Rotational variation of the linear polarization of the asteroid (3200) Phaethon as evidence for inhomogeneity in its surface properties★. (1st August 2018) - Borisov, G; Devogèle, M; Cellino, A; Bagnulo, S; Christou, A; Bendjoya, Ph; Rivet, J-P; Abe, L; Vernet, D; Donchev, Z; Krugly, Yu; Belskaya, I; et al.
ABSTRACT: Asteroid (3200) Phaethon is a Near-Earth Apollo asteroid with an unusual orbit that brings it closer to the Sun than any other known asteroid. Its last close approach to the Earth was in 2017 mid-December and the next one will be on 2026 October. Previous rotationally time-resolved spectroscopy of Phaethon showed that its spectral slope is slightly bluish, in agreement with its B/F taxonomic classification, but at some rotational phases, it changes to slightly reddish. Motivated by this result, we performed time-resolved imaging polarimetry of Phaethon during its recent close approach to the Earth. Phaethon has a spin period of 3.604 h, and we found a variation of the linear polarization with rotation. This seems to be a rare case in which such variation is unambiguously found, also a consequence of its fairly large amplitude. Combining this new information with the brightness and colour variation as well as previously reported results from Arecibo radar observations, we conclude that there is no variation of the mineralogy across the surface of Phaeton. However, the observed change in the linear polarization may be related to differences in the thickness of the surface regolith in different areas or local topographic features.